Respuesta :
Answer:
x = 1.074
x = -0.931
Step-by-step explanation:
The given expression is 7x² - x = 7
7x² - x - 7 = 0
Now we apply the quadratic formula in the given expression to find the value of x.
Since quadratic formula is
[tex]x=\frac{b\pm \sqrt{b^{2}-4ac}}{2a}[/tex]
So we put the value of b = -1, a = 7 and c = -7
x [tex]=\frac{+1\pm \sqrt{(-1)^{2}-4(7)(-7)}}{2(7))}[/tex]
[tex]=\frac{1\pm \sqrt{1+196}}{14}[/tex]
[tex]=\frac{1\pm \sqrt{197}}{14}[/tex]
[tex]x=\frac{1\pm 14.035}{14}[/tex]
x = 1.074
x = -0.931